English Children’s Literature: Traditions, Sources, And Cultural Influence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article analyzes the features of the formation and development of English children’s literature, its connection with folklore and national history. The mythological origins, the influence of historical and cultural processes, and the interaction between children’s and adult literary traditions are examined. It is concluded that English children’s literature represents a unique cultural phenomenon that combines both educational and aesthetic functions.